Individualized dynamic PEEP (dynPEEP) vs. positive pressure ventilation in delivery room management: A retrospective cohort study - Song, Sijie; Zhu, Yefang; Li, Jie; Wang, Qi; Gong, Hua; Zhong, Xiaoyun; Wu, Yan (Frontiers in Pediatrics, 2023)
Objective: Although nasal continuous positive airway pressure (nCPAP) is recommended in delivery room (DR) management for preterm infants, the effect of delivering nCPAP at 6-8 cmH2O is not satisfactory. Therefore, we conducted this retrospective cohort study to compare the effects of individualized dynamic positive end-expiratory pressure (dynPEEP) versus positive pressure ventilation (PPV) in the DR on clinical outcomes. Methods: Preterm infants with a gestational age (GA) less than 30 weeks who received PPV (peak inspiratory pressure, PIP/PEEP 15-25/6-8 cmH2O) from August 2018 to July 2020 were included as Cohort 1 (PPV group, n = 55), and those who received dynPEEP (nCPAP 8-15 cmH2O) from June 2020 to April 2022 were included as Cohort 2 (dynPEEP group, n = 62). Primary outcomes included the DR intubation rate and the bronchopulmonary dysplasia (BPD) rate. The secondary outcomes included DR stabilization, transfer, admission, respiratory function, and other outcomes. Results: The percentage of singleton infants was higher in the PPV group (63.6%) than in the dynPEEP group (22.6%, p = 0.000). The DR intubation and chest compression rates were higher in the PPV group (80.0% and 18.2%, respectively) than in the dynPEEP group (45.2%, p = 0.000; 3.0%, p = 0.008, respectively). The percentage of patients with 5-min Apgar scores < 5 was higher in the PPV group (9.1%) than in the dynPEEP group (0%, p = 0.016). The partial pressure of carbon dioxide was lower in the PPV group (49.77 ± 11.28) than in the dynPEEP group (56.44 ± 13.17, p = 0.004), and lactate levels were higher in the PPV group (3.60 (2.10, 5.90)) than in the dynPEEP group (2.25 (1.38, 3.33), p = 0.002). No significant differences in the BPD rate or other secondary outcomes were noted. Conclusions: In this retrospective cohort study, the dynPEEP strategy reduced the need for DR intubation compared with PPV. The dynPEEP strategy is feasible and potentially represents an alternative respiratory strategy to PPV. Nevertheless, a randomized control trial is needed to evaluate the dynPEEP strategy.